The Effect of a Guided Inquiry Learning Model Based on E-Modules on Students’ Problem Solving Skills - Sri Minarni Rezeki; Kartini Rahman Nisa; Jayadin Jayadin (IAIN Sorong, 2026)
This study aims to examine the effect of a guided inquiry learning model based on E-Modules on students’ problem-solving abilities. The research was conducted at SMA St. Petrus Kewapante. The sample consisted of 20 students, all of whom were included in the study. This research employed a quantitative method, which is based on objective measurement of numerical data to test the formulated hypotheses. The test results were analyzed statistically to determine significance, with the expectation of obtaining objective, measurable, and generalizable data in accordance with the population characteristics. The findings indicate a significant improvement in students’ problem-solving abilities after the implementation of the guided inquiry learning model based on E-Modules. This is evidenced by a statistically significant difference between pretest and posttest mean scores (p < 0.001) and an N-Gain score in the moderate category (mean = 0.5024 or 50.24%). Furthermore, the results of normality and homogeneity tests show that the data are normally distributed and homogeneous, indicating that the parametric statistical analysis used is valid and reliable.